Implementasi Integrasi Sapi - Kelapa Sawit dan Dampaknya Terhadap Efisiensi Biaya Produksi Kelapa Sawit di Desa Sangkir Indah Kabupaten Rokan Hulu - Melani, Ana; Hidayat, Tommi; Rasyid, Erwin; Wicaksana, Indrajit (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2023)
The oil palm cattle integration activity was initiated by the central government with the Revitalization of Animal Husbandry and Forestry Agriculture (RPPK) in 2005. The goal of the oil palm cattle integration activity is to create a symbiosis of mutualism for each commodity using efficiency in the cost of oil palm production, increasing farmers' income to achieve the welfare of farmers. The sustainability of the integration of cattle-oil palm is a manifestation of the empowerment of farming communities so that they are still carrying out these activities. Integration of cattle–oil palm is the management of oil palm plantations and cattle breeding together. The research aims to find out how much the cost efficiency of oil palm production is in the sustainability of cattle–oil palm integration activities. Data collection techniques through interviews, observation and documentation. Data analysis using descriptive quantitative. The results showed that there was efficiency in the cost of producing palm oil after integrating cow-oil palm with a percentage of 80% with many categories. This means that the cattle–oil palm integration activities provide relative advantages to the farmers who carry out these activities. This was caused by the use of organic fertilizers of 84.6% and efficiency in labor costs, cattle care and oil palm of 75.4%. Integration patterns carried out by farmers are intensive, extensive and semi-intensive patterns. Integration also has an impact on the availability of self-made organic fertilizers for the management of land owned.